Sensitivity of the early-life stages of freshwater mollusks to neonicotinoid and butenolide insecticides. (November 2016) - Prosser, R.S.; de Solla, S.R.; Holman, E.A.M.; Osborne, R.; Robinson, S.A.; Bartlett, A.J.; Maisonneuve, F.J.; Gillis, P.L.
Abstract: Neonicotinoid insecticides can be transported from agricultural fields, where they are used as foliar sprays or seed treatments, to surface waters by surface or sub-surface runoff. Few studies have investigated the toxicity of neonicotinoid or the related butenolide insecticides to freshwater mollusk species. The current study examined the effect of neonicotinoid and butenolide exposures to the early-life stages of the ramshorn snail, Planorbella pilsbryi, and the wavy-rayed lampmussel, Lampsilis fasciola . Juvenile P. pilsbryi were exposed to imidacloprid, clothianidin, or thiamethoxam for 7 or 28 d and mortality, growth, and biomass production were measured. The viability of larval (glochidia) L. fasciola was monitored during a 48 h exposure to six neonicotinoids (imidacloprid, thiamethoxam, clothianidin, acetamiprid, thiacloprid, or dinotefuran), or a butenolide (flupyradifurone). The 7-d LC50s of P. pilsbryi for imidacloprid, clothianidin, and thiamethoxam were ≥4000 μg/L and the 28-d LC50s were ≥182 μg/L. Growth and biomass production were considerably more sensitive endpoints than mortality with EC50s ranging from 33.2 to 122.0 μg/L. The 48-h LC50s for the viability of glochidia were ≥456 μg/L for all seven insecticides tested. Our data indicate that neonicotinoid and butenolide insecticides pose less of a hazard with respect to mortality of the two species of mollusk compared to the potential hazard to other non-target aquatic insects. Graphical abstract: Highlights: LC50s of glochidia viability for neonicotinoids and butenolides were >500 μg/L. Neonicotinoids and butenolides represent a de minimis risk to glochidia. 7-d LC50s were >3000 μg/L and 28-d LC50s were >150 μg/L. Growth was a more sensitive endpoint of exposure than mortality for juvenile snails. Hazard quotients for growth and biomass production of juvenile snails were >1. Abstract : Neonicotinoid or butenolide insecticides pose a de minimis risk to glochidia of Lampsilis fasciola but could represent a hazard to the growth and biomass production of juvenile snails.